Pengarahan dan Pelatihan Pengembangan SDM Untuk Meningkatkan Kinerja Pada PT Simed Prakarsa Indonesia - Supardi Supardi (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2018)
The purpose of this study was to determine the direction and training of HR development to improve the performance of PT Simed Prakasa Indonesia. This study uses qualitative research methods, research methods that are based on the philosophy of postpositivism. The results in this study employees are very enthusiastic and willing to follow directions from the leadership to improve employee performance at PT. Simed Prakarsa Indonesia. Produce a logically and comprehensively related framework to develop an environment where employees are encouraged to develop learning. performance resulting from individual work and specific activity behaviors during a certain period of time which includes individual work outcomes such as the quality and quantity of work, employee behavior, such as ability, personality, work sincerity and work discipline, and characteristics that include good, confident, cooperative ability, and leadership. So that PT. Simed Prakarsa Indonesia can improve employee performance both theoretically and technically as well as direction and employee development carried out aiming to improve the technical, theoretical, and moral capabilities of employees so that their performance is better and achieve optimal results. While the factors that can be used as an assessment of the performance of employees of PT. Simed Prakarsa Indonesia is work and personal potential.